'Telling lies on behalf of the Bible': S. R. Gardiner's Doubts about Catholic Apostolic Teaching. (16th June 2016) - Grass, Tim
Abstract : The reasons for the historian Samuel Rawson Gardiner's departure from the Catholic Apostolic Church in the mid-1860s are speculated upon but not generally known. This essay makes use of letters, hitherto in family hands and unknown to researchers, from Gardiner and his wife Isabella to her brother Martin Irving in order to trace the growth of Gardiner's doubts and his alienation from the Catholic Apostolic Church. In particular, the letters show how Gardiner felt the Church was mishandling the intellectual challenges exercising contemporary churchmen. The aim is to shed light on an aspect of Gardiner's biography which has not previously been explained adequately, and so to illuminate the response of one conservative religious movement – the Catholic Apostolic Church – towards the challenges presented by developments in the disciplines of geology and Biblical studies. It is argued that for Gardiner doubt was a necessary function of the quest for truth.